Carbon monoxide exposures among U.S. wildland firefighters by work, fire, and environmental characteristics and conditions. Issue 12 (2nd December 2019) - Henn, Scott A.; Butler, Corey; Li, Jia; Sussell, Aaron; Hale, Christa; Broyles, George; Reinhardt, Timothy
Abstract: Carbon monoxide (CO) exposure levels encountered by wildland firefighters (WLFs) throughout their work shift can change considerably within a few minutes due to the varied tasks that are performed and the changing environmental and fire conditions encountered throughout the day. In a U.S. Forest Service study during the 2009–2012 fire seasons, WLFs from 57 different fires across the U.S. were monitored for CO using CO data-logging detectors while an observer recorded worker tasks, fire characteristics, and environmental conditions at scheduled intervals. Exposures to CO for 735 WLF's work shifts were analyzed to assess the effect of variations among work tasks, fire characteristics, and environmental conditions. Geometric mean full shift time-weighted averages were low at 2.4 parts per million (ppm) and average length of work shift was 11 hr and 15 min. The task with the highest mean CO exposure was sawyer/swamper at 6.8 ppm; workers performing that task had an estimated 9 times higher odds of a having a 1-min CO measurement exceeding 25 ppm than the referent pump task (OR = 8.89, 95% CI = 1.97, 40.24). After adjusting CO exposure limits for shift length, elevation, and work level, 2% and 4% of the WLF's work shifts exceeded the National Institute for Occupational Safety and Health's recommended exposure level and the American Conference of Governmental Industrial Hygienist's threshold limit value, respectively. In regression modeling, variables that were significantly associated with elevated levels of CO exposure included: task, fuel model, wind orientation, crew type, relative humidity, type of attack, and wind speed. In the absence of instruments such as CO detectors that can determine and alert WLFs to elevated CO levels, recognition of the conditions that lead to elevated levels of CO exposure can assist WLFs to effectively use administrative controls, such as work rotations, to minimize exposures.